Damage detection in elements of structures by the elastic wave propagation method - Ostachowicz, Wiesław; Żak, Arkadiusz; Kudela, Paweł; Krawczuk, Marek (Computer Assisted Methods in Engineering and Science, 2006)
This paper presents certain results of the analysis of elastic wave propagation in one-dimensional (1-D) andtwo-dimensional (2-D) elements of structures with damage. The problem of the elastic wave propagation has been solved by the use of the Spectral Element Method (SEM) . In this approach elements of structures are modelled by a number of spectral finite elements with nodes defined at appropriate Gauss-Lobatto-Legendre points. As approximation polynomials high order orthogonal Lagrange polynomials are used. In order to calculate the elements characteristic stiffness and mass matrices the Gauss-Lobatto quadrature has been applied. In the current analysis damage in the form of crack has been considered. It has been assumed that the damage can be of an arbitrary length, depth, and location and can be simulated as a line spring of varying stiffness. Numerical calculations illustrating the phenomena of the elastic wave propagation in isotropic media have been carried out for the case of an aluminium rod and beam as well as a flat aluminium panel and plate.